PERANCANGAN MODEL PENILAIAN KINERJA METODE 360 PADA KANTOR PERUMDA PARKIR MAKASSAR RAYA - Saputra, Muh. Oky; Musdalifah, Musdalifah; Al Fajery, Muhammad Rifqy (Politeknik STIA LAN Makassar, 2024)
A one-way assessment system on Perumda Parkir Makassar Raya is an assessment method that only collects information from one source and there is a high possibility of bias in evaluating employee performance. This may cause problem because a subjective assessment system will have an impact on the remuneration system and the distribution of responsibilities will be unfair, therefore This research was conducted with the aim of avoiding bias in assessment and creating a fair and supportive work environment with the concept of 360 degree assessment. The research method used is descriptive qualitative to describe conditions through descriptions of phenomena that occur in the field and provide a detailed picture of related problems as well as assisting researchers in creating assessment models using a 360 degree concept for more objective performance measurement and being able to overcome problems. The results of this research have an impact on employee satisfaction levels because the 360 ​​degree assessment concept is considered more efficient to carry out and employee performance measurement becomes clearer and can increase employee work motivation.